The Relationship Among Life Style, Coping Strategies and Religiosity With General Health in Iranian Students - Jamal Ashoori; Mohammad Ashoori (International Journal of Public Health Science (IJPHS), 2013)
General health has been associated with many variables that from most important can be noted Life Style, Coping Strategies and Religiosity. This study examined the relationship between life style, coping strategies, religiosity and general health among Iranian students. This cross sectional study was conducted on 180 students 15-17 year olds who were selected via multi step cluster sampling method design from schools in the Varamin suburb, Iran in 2013. All students completed the questionnaires of life style, coping strategies, religiosity and general health and regression was used for data analyses. The statistical analysis revealed a positive relationship between life style, problem solving strategy and internal religiosity with general health (P<0.01) and a negative relationship between emotional coping strategy with general health (P<0.05). Life style, internal religiosity and problem-focused strategy predicted 32 percent of variance of general health and also share of life style in prediction general health was over of other variables. These results highlight the importance in considering life style at further understanding general health in students.DOI: http://dx.doi.org/10.11591/ijphs.v2i3.3940